ANALYSIS OF DEATHS DUE TO ROAD TRAFFIC ACCIDENTS IN FAISALABAD CITY- PAKISTAN - Kishwar Naheed; Mobin Inam Pal; Muhammad Naeem; Altaf Pervez Qasim; Sadaf Yunis; Zuneera Misbah (Journal of University Medical & Dental College, 2019)
OBJECTIVE: To analyze the deaths due to road traﬃc accidents in Faisalabad City and to ﬁnd out the demographic proﬁle of the victims with reference to the site of fatal injuries observed during autopsies. STUDY DESIGN: Retrospective study. SETTING & DURATION: Study was conducted in the Department of Forensic Medicine, Faisalabad Medical University, Faisalabad for a period of ﬁve years from 1st January, 2013 to 31st December, 2017. METHODOLOGY: The dead bodies of 276 victims died of RTAs were brought for postmortem examinations during study period of three years. Data collected by examining the record of all medico-legal autopsies using convenient sampling & entered in a predesigned performa for detailed analysis. RESULTS: Of the total 276 autopsies conducted in Postmortem unit of Faisalabad Medical University, Faisalabad; 225(81.52%) cases were male and 51(19.48%) females. And out of those 225 males; 47(20.9%) belonged to the age group of 20-29 years whereas from 51(19.48%) females cases 11(21.6%) belonged to the age group of 20-29 years. The ratio of male to female was 4.41:1. The percentage of deaths due to RTA remained 92(33.3%) which were the highest during 2013 to 2017. Highest numbers of victims being 30(11%) and 30(11%) respectively were reported in the month of March & April. CONCLUSION: Male proportion was higher than the females. Spring season was very sensitive for RTAs. Head & Chest were the most commonly involved sites. The law enforcement agencies should control and create awareness in masses regarding the measures for road safety. However, the traﬃc rules should be implemented in letter & spirit.